The Complete Guide to Antiques - Miller, Martin, 1946-2013 (London Carlton, 2003)
A collection of over 6000 antiques of every variety. Every entry is illustrated by a colour photograph and includes information on dealer prices, date and origin, which will assist you in identifying and valuing your own antiques, as well as helping you find and pay the right price for something you desire.
Include Index and Illustration
Keywords: Antiques -- Antiques--Prices -- Collectibles